Bacterial community responses of the hydrothermal vent crab Xenograpsus testudinatus fed on microplastics - Muthu, Priyanka; Lee, Yun-Cheng; Girija, Gowri Krishna; Chen, Yu-Ling; Ho, Ying-Ning; Hwang, Jiang-Shiou (Frontiers in Ecology and Evolution, 2023)
Microplastics (MPs) provide persistent contaminants in freshwaters and the oceans from anthropogenic sources worldwide. Microplastics contamination in ecosystems has emerged as a global environmental issue. While increasing research focused on the ecological consequences of plastic pollution, health-related implications of plastic pollution have been somewhat overlooked. In this study we evaluated the effects of polyethylene microplastic contamination on microbial, physical, biochemical characteristics of the hydrothermal vent crab Xenograpsus testudinatus over a 7-day food exposure. Different concentrations (0%, 0.3%, 0.6%, 1.0%) of polyethylene microplastics were used for feed intake experiments. Oxford Nanopore Technology full length sequencing of the 16S rDNA gene was used to explore the changes of the microbial composition in vent crab tissues. At the phylum level, the content of Firmicutes significantly decreased in the digestive gland tissue. Furthermore, the predicted function of genes in the microbial community were significantly influenced by MPs. In contrast, were 8 functions in gill and 11 functions in digestive gland tissues identified at low and high intake levels. The dominant function of methylotrophy, dark thiosulfate oxidation, dark oxidation of sulfur compounds, aromatic hydrocarbon degradation and aromatic compound degradation were significantly increased at high intake levels in the digestive gland. These findings indicate that microplastic ingestion causes not only a short-term decrease in energy intake for crustaceans, but also a change in microbial communities and their functions. This study provided a first account on the toxicity of MPs in a hydrothermal vent crab to aid in the assessment of health risks provided by polyethylene MP to marine invertebrates.